The impact of structural disadvantage on the gender-gap and sex-specific rates of nonlethal violent victimization - Powers, Ráchael A. (Crime & delinquency, 2018)
This study examined the gendered impact of structural disadvantage and economic inequality on two forms of nonlethal victimization (assault and robbery). Compared with research on the gendered impact of structural disadvantage on perpetration, few studies have examined the differential susceptibility of men and women’s risk of victimization. We use data from the City of Los Angeles (2001-2007) to examine the relative influence of neighborhood characteristics on both the gender gap in victimization as well as sex-specific measures of assault and robbery victimization. In general, we largely find that neighborhood disadvantage and economic inequality do little to explain the gender gap in victimization; however, structure plays a more significant role in understanding sex-specific victimization rates, but the relationship varies by crime type.